Fostering MSMEs to Increase Fintech-Based Financial Literacy - Candraningrat, I.R.; Darmayanti, N.P.A.; Damayanthi, I.G.A.E.; Nurcaya, I.N. (Devotion : Journal of Research and Community Service, 2023)
The existence of fintech lending can be a solution for MSMEs in obtaining capital, but there are still many MSMEs who do not know what and how the mechanism for obtaining capital through fintech is. It is important to introduce the benefits and dangers of information technology-based lending and borrowing services (Fintech Lending) to MSMEs in Badung Market to increase access to capital so as to increase competitiveness and expand markets, because in addition to the many benefits there are risks involved, so that SMEs understand earlier what risks will be faced from the convenience that is obtained. This community service aims to provide socialization to MSMEs regarding the existence of fintech lending as an alternative source of business funding. Increase insight into information technology-based money-lending services so that you are not fooled by tempting offers.